When US sneezes, clichés spread: How do the commodity index funds react then?. (December 2020) - Awasthi, Kritika; Ahmad, Wasim; Rahman, Abdul; Phani, B.V.
Abstract: This study examines the financialisation aspect of major commodities traded on the US market platforms. Our main aim is to measure the sensitivity of the Goldman Sachs Commodity Index (GSCI) and its sub-indices energy and precious metals: gold and silver, with economic uncertainty and financial stress of the US economy. We do this exercise in two steps. First, we examine the sensitivity of GSCI, and its sub-indices with the US-linked economic uncertainty, financial stress, and stock market implied volatility. In the second step, we introduce the implied volatilities of energy and precious metals and analyse their quantile-based causal dependence structure. The estimates of Granger-causality in quantiles suggest that the US-linked economic uncertainty, financial stress, and stock market implied volatility significantly explain the GSCI and its sub-indices at the lower and higher quantiles. Economic uncertainty exhibits stronger impact than financial stress. The comovement between stock market implied volatility and GSCI indices suggests the deepening of the financialisation process. Overall, the sensitivities and dependence structures of US economic and financial risk factors are better explained by the Quantile cointegration and Granger-causality in quantile models. Highlights: The commodity index funds exhibit dependence with uncertainty and financial stress variables of the US economy. Economic uncertainty has a more substantial impact than financial stress. The commodity market shows the presence of financialisation process.